Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.19102/icrm.2021.120505
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Durability in Radiofrequency Ablation of Atrial Fibrillation

Abstract: Radiofrequency ablation (RFA) remains a highly effective therapy in the management of paroxysmal atrial fibrillation (PAF) and is an important therapeutic option in the management of persistent atrial fibrillation (PeAF) when clinically indicated. Lesion size is influenced by many parameters, which include those related to energy application (RFA power, temperature, and time), delivery mechanism (electrode size, orientation, and contact force), and the environment (blood flow and local tissue contact, stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
0
1
0
Order By: Relevance
“…Advancements in CF, power, energy delivery parameters, catheter stability information (Fig. 2 .8), and the understanding of lesion biophysics have led to the development of ablation indexes (AIs) that can objectively assess lesion creation and durability during RFA [ 56 , 57 ]. Commercially available AIs, such as the Lesion Index (Abbott, Green Oaks, IL, USA) and the CARTO VISITAG™ Module (Biosense Webster, Irvine, CA, USA), integrate stability, CF, time, and power to aid in optimizing lesion formation.…”
Section: Ablation Lesion Assessments Are We Using the Appropriate Tools?mentioning
confidence: 99%
See 2 more Smart Citations
“…Advancements in CF, power, energy delivery parameters, catheter stability information (Fig. 2 .8), and the understanding of lesion biophysics have led to the development of ablation indexes (AIs) that can objectively assess lesion creation and durability during RFA [ 56 , 57 ]. Commercially available AIs, such as the Lesion Index (Abbott, Green Oaks, IL, USA) and the CARTO VISITAG™ Module (Biosense Webster, Irvine, CA, USA), integrate stability, CF, time, and power to aid in optimizing lesion formation.…”
Section: Ablation Lesion Assessments Are We Using the Appropriate Tools?mentioning
confidence: 99%
“…However, its implementation is currently limited to right-sided procedures, and more data are needed to establish its use in LA ablation or in the left ventricle [ 70 , 71 ]. Challenges include the correlation between T-2 edemas and long-lasting lesions and the time required for LGE to be fully established, in addition to the EP laboratory device and equipment compatibility limitation, which remains a major area of concern [ 57 , 71 ]. Additionally, studies have revealed that utilizing an MRI-guided, fibrosis-targeted ablation with PVI did not significantly improve ablation outcomes.…”
Section: Ablation Lesion Assessments Are We Using the Appropriate Tools?mentioning
confidence: 99%
See 1 more Smart Citation
“…A beneficial effect of radiofrequency ablation (RFA) on quality of life has been suggested by several studies, [11,12] but it is unclear whether the effect of RFA on quality of life is sustained, because long-term follow-up data have been limited. The optimal therapeutic approach for AF is still debated and no randomized controlled trials (RCTs) have been sufficiently powered to address these issues.…”
Section: Introductionmentioning
confidence: 99%